Who plans the planning architecture, politics and mankind - Burckhardt, Lucius (Birkhäuser, 2020)
From the 1950s, Lucius Burckhardt (1925-2003) focused on planning, design, and construction in a democracy. His astute observations and critical analysis have had a fundamental effect on the design of our environment, on teaching in the architectural/planning professions, and on our understanding of what "city" means. His research, which - between mighty commercial interests and conflicting political aspirations focuses on the benefit for the entire population - is indispensable when and wherever buildings are planned, designed, built, and inhabited. With a new selection of texts, this book ploughs a furrow through Lucius Burckhardt's theory of planning.